Impacts of Sovereign Rating on Sub-Sovereign Bond Ratings in Emerging and Developing Economies - Mohapatra, Sanket; Nose, Manabu; Ratha, Dilip (World Bank, Washington, DC, 2016)
This paper explores bond-level, issuer-level, and macro-level conditions that affect the distance between sovereign credit rating and sub-sovereign debt ratings. Over three-quarters of rated foreign-currency sub-sovereign bonds issued during 1990–2013 in 47 emerging and developing countries were rated at or below the corresponding sovereign rating, thus confirming the prevalence of a sovereign ceiling. For bonds rated below the sovereign ceiling, a Tobit regression shows strong sovereign-corporate links for financial firms, publicly-owned firms, and local government entities. International bonds tend to be rated closer to the sovereign rating during riskier global financial conditions. Well-developed domestic financial markets also tend to be related to a smaller distance, likely because of stronger macro-financial links for financial issuers. About 11 to 26 percent of the bonds had ratings higher than the sovereign rating, which was achieved mainly through securitization structures. This observation is confirmed using a double-hurdle estimation that accounts for bond and firm characteristics and macroeconomic conditions. The sovereign-corporate rating relationship became significantly stronger at the peak period of the 2008-09 global financial crisis, and appears to have weakened in the subsequent years.